Newcomer knowledge, attitudes, and beliefs about human papillomavirus (HPV) vaccination - Wilson, Lindsay A; Quan, Amanda M L; Bota, A. B; Mithani, Salima S; Paradis, Michelle; Jardine, Cindy; Hui, Charles; Pottie, Kevin; Crowcroft, Natasha; Wilson, Kumanan (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Human Papillomavirus (HPV) is the most common sexually transmitted infection in Canada and around the world. Vaccination is an effective prevention strategy, but uptake is low, especially among newcomers to Canada. We sought to understand newcomers’ knowledge, attitudes, and beliefs (KAB) on HPV and HPV vaccination and their role in HPV vaccine acceptance. Methods Newcomers were defined as individuals born outside Canada, (i.e., individuals born in a different country, the majority of whom are immigrants or refugees, but also includes students and undocumented migrants). Eligible participants were newcomers, aged 16 or older and who could read or write in English, French or Arabic. Surveys were administered in two community health centres in Ottawa, Canada that primarily engage with newcomer populations. Follow-up interviews were conducted either at the community health centre or over the phone, depending on participants’ preferences. Results Fifty participants completed the survey, the majority of whom were women (74%) and spoke Arabic as their first language (54%). Seven participants completed supplemental interviews to complement their survey responses. The majority (70%) of participants had not previously heard of HPV. Less than half (46%) knew that the vaccine is effective in preventing certain types of cancer; nearly 40% incorrectly believed the vaccine could cure HPV. Qualitative interviews supported the survey findings. Conclusions Despite a lack of HPV knowledge due to cultural and language barriers, there is still a strong desire among newcomers to receive the vaccine, especially when accompanied by a physician recommendation. Cultural and language-appropriate resources are needed to help newcomers make informed vaccination decisions and promote HPV vaccine uptake.